Development of a Clay Biodigester - Nathan, C.; Bwala, E. B.; Barnabas, A, A,; Damilare, A. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
The quest for sustainable waste management, reduction of greenhouse gas emission and the increasing demand of energy has led researchers to seek for alternative solution in meeting both demands. Anaerobic digestion technology is used for digesting wastes and producing biogas, which is a source of renewable energy in return. This research work examines the use of clay as an alternative construction material of the anaerobic biodigesters. The biodigesters were carefully designed to ensure airtightness and to attain an anaerobic environment inside the digesters. Clay in its nature tends to retain heat received, abundance in nature and is of low cost. The ability of clay material to retain heat makes it viable for biodigester, as temperature is one of the key parameters in the production of biogas. It employed the prototype and evaluated the rate at which clay biodigester produced biogas as compared to other construction materials. Five (5) different biodigesters containing different sample compositions were used for the experiment. The first biodigester is the control containing 8kg of cow dung mixed with 16kg of water. The second biodigester contains 4kg of cow dung, 4kg of beans chaff mixed with 16kg of water. The third biodigester contains 2kg of cow dung, 2kg of vegetables mixed with 16kg of water. The fourth biodigester contains 3kg of cow dung, 3kg of beans chaff, 3kg of vegetables mixed with 16kg of water. The fifth biodigester contains 4kg of cow dung, 4kg of goat excreta mixed with 16 kg of water. The biodigesters were evaluated under the same anaerobic condition. It was observed that the biodigester with the cow dung and beans chaff combination produced the highest biogas with an average daily production of 0.41litre/day. The biodigester with cow dung, and vegetables gave an average daily production of 0.35litre/day. The biodigester with cow dung and beans chaff gave an average daily production of 0.384litres/day. The biodigester with cow dung and goat excreta gave an average daily production of 0.352litre/day. The biodigester with cow dung only gave an average daily production of 03.6litres/day. All the experiments were carried out on an average daily temperature of 29℃. Each one of the biodigesters have an uptrend line i.e. the higher the retention period, the more the biogas produced. It was also observed that biogas production depends greatly on the temperature of the environment. This is to make biodigesters and green energy easily accessible to the local communities.